Effect of two different primers on the shear bond strength of metallic brackets to zirconia ceramic - Alexander Franz; Modesto Raabe; Bledar Lilaj; Rinet Dauti; Andreas Moritz; Dieter Müßig; Barbara Cvikl (BMC, 2019)
Abstract Background In view of the increasing demand of adult orthodontics for esthetic purposes, adult treatment with brackets has become an important issue. One essential factor for the quality of such treatment is bracket bonding on ceramics. For testing the adhesive bond between the bracket and the ceramic surface it is important to consider the static or cyclic loading that goes along with it. Methods Metallic Brackets were adhesively fixed on zirconia ceramic blocks in a simulated leveling phase using two different primers (Monobond S and Monobond Etch & Prime). Half of the metallic brackets were activated using a 0.14-nickel titanium wire, while the other half remained non-activated. Shear bond testing (SBT) was performed after thermocycling. Furthermore the Adhesive Remnant Index (ARI) was analyzed. Results SBT resulted in significantly higher shear bond values when Monobond Etch & Prime was used compared to the use of Monobond S. Activation of the brackets did not show different results in comparison to the non-activated brackets. The ARI did not indicate cement remnants on the ceramic surface, regardless of the primer and the activation status. Conclusions The use of Monobond Etch & Prime has great potential for the bonding of brackets on dental zirconia ceramics.